2005
DOI: 10.1081/ncn-200061780
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy of Respiratory Syncytial Virus by 2-5a Antisense

Abstract: Respiratory syncytial virus is a leading cause of respiratory disease in infants, young children, immunocompromized patients, and the elderly. Previous work has shown that RNase L, an antiviral enzyme of the interferon system, can be recruited to cleave RSVgenomic RNA by attaching tetrameric 2' 5'-linked oligoadenylates (2 5A) to an antisense oligonucleotide complementary to repetitive intergenic sequences within the RSV genome (2 5A antisense). RBI034, a 2'-O-methyl RNA-modified analogue of the 2 5A anti-RSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…RBI034 was also effective in reducing viral titres in cotton rats when delivered by aerosol for 15 min/day using a reservoir concentration of 50 mg/ml in water (Figure 9). Similar results were found for RBI245 [128]. In comparison, cotton rats need to be treated for a minimum of 2 h a day with ribavirin at such concentrations to be effective [130][131][132][133].…”
Section: -5a Antisense -Targeting Respiratory Syncytial Virus Througsupporting
confidence: 64%
See 2 more Smart Citations
“…RBI034 was also effective in reducing viral titres in cotton rats when delivered by aerosol for 15 min/day using a reservoir concentration of 50 mg/ml in water (Figure 9). Similar results were found for RBI245 [128]. In comparison, cotton rats need to be treated for a minimum of 2 h a day with ribavirin at such concentrations to be effective [130][131][132][133].…”
Section: -5a Antisense -Targeting Respiratory Syncytial Virus Througsupporting
confidence: 64%
“…Combination treatment of IFN and RBI245 at low concentrations also demonstrated synergistic protection against RSV infection in cell culture (Figure 6). RBI034 and RBI245 were found to be effective in reducing RSV infections in three different animal models [128]. RBI245 reduced viral titres from > 2000 to ∼ 100 plaque-forming units in mice when RBI245 was given intranasally at a concentration of 10 mg/kg every other day on days 1, 3 and 5 after, and once 6 h before RSV infection (Figure 7).…”
Section: -5a Antisense -Targeting Respiratory Syncytial Virus Througmentioning
confidence: 96%
See 1 more Smart Citation
“…However, no single animal model presents the complete spectrum of the disease observed in humans. Several primate models have been successfully used to demonstrate the prophylactic or therapeutic efficacy of human RSV antivirals (8,9,14,17). Small-rodent models of human RSV infection such as BALB/c mice and cotton rats (Sigmodon hispidus) have not only contributed to the understanding of the pathogenesis and immunobiology of human RSV disease but have also been used to demonstrate the in vivo efficacy of antiviral agents (1,7,10,13,14,19,20,27,28).…”
mentioning
confidence: 99%
“…Despite concerns about nonspecific effects, however, ASOs have very acceptable toxicity profiles. 27,30,31 ASOs are now being widely evaluated for the treatment of many diseases, including muscular dystrophy, 32 hypertension, 30,33 viral infections, 34 and cancer. 27,31 Previous studies have shown that ASOs to different collagen subtypes have been successful in reducing the expression of the targeted mRNA in different cell lines.…”
mentioning
confidence: 99%